PENGARUH INDEPENDENSI DAN KOMPETENSI TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH (STUDI PADA INSPEKTORAT KOTA KENDARI) - Hasbudin, Hasbudin; Tamburaka, Sulvariani; Supriati, Titin (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aimed to examine the effect of Independence and competence of the audit quality Inspectorate officers in the area of financial supervision in Kendari city Inspectorate. The population of this research is the functional groups totaling 28 people, with the sample collection method is a method of census. Data taken from the questionnaire distributed to respondents. Perceptions of respondents measured by the questionnaire answers using ordinal measurements with a 5-point Likert scale. The statistical method used to test each hypothesis is Multiple Regression Analysis.Â The results of this study indicate that the independence and competence have a significant effect on audit quality apararat Inspectorate in the area of financial supervision. The coefficient of determination shows that jointly independence and competence contribute to audit quality by 85.4%, while the remaining 14.6% influenced by other factors outside the model. Implications of these findings for efforts to achieve a quality audit is the need to increase the independence both independence in fact and independence in appearance and increase competence by conducting training and certification office.Keywords: Independence, competence and quality audit